2020
DOI: 10.11648/j.jhrm.201200803.12
|View full text |Cite
|
Sign up to set email alerts
|

Enterprise Social Media (ESM) Use and Employee Belongingness in US Corporations

Abstract: This study explored social capital theory by investigating the relationship between enterprise social media use (ESM) as measured by an adapted instrument and employee belongingness as measured by the balanced measure of psychological needs (BMPN) scale of employees in USA, moderated by generational age groups. A survey of 155 employees from US corporations was conducted. The results support the theoretical model of social capital as well as three hypothesized relationships. While there was no significant rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…We note that some studies find diverging associations between using ESM for workconsistent vs. inconsistent or social purposes and well-being (Labban & Bizzi, 2021;Liang et al, 2020;Randall et al, 2020). For example, work-inconsistent ESM use is associated with higher job satisfaction, but work-consistent ESM use is not (Liang et al, 2020).…”
Section: Work-consistent Vs Work-inconsistent Usementioning
confidence: 65%
“…We note that some studies find diverging associations between using ESM for workconsistent vs. inconsistent or social purposes and well-being (Labban & Bizzi, 2021;Liang et al, 2020;Randall et al, 2020). For example, work-inconsistent ESM use is associated with higher job satisfaction, but work-consistent ESM use is not (Liang et al, 2020).…”
Section: Work-consistent Vs Work-inconsistent Usementioning
confidence: 65%
“…There has been prior research in social media contexts that have provided evidence of a broad range of benefits to individuals associated with the use of social media sites. Randall et al (2020) found that in the context of work using social media technologies can assist employees feel that they are a part of the social makeup of the organization. From a professional perspective, social media serves as a tool to grow your professional network.…”
Section: Perceived Benefitmentioning
confidence: 99%
“…The literature review uncovered the impact of ESM use on employee outcomes , such as – employees' workplace anxiety (Wang et al. , 2022b), employee belongingness (Randall et al ., 2020), knowledge sharing (Sun et al ., 2019a, b; Masood et al ., 2022) and knowledge transfer (Sun et al ., 2020) – to name a few.…”
Section: Literature Reviewmentioning
confidence: 99%